Pengujian Kualitas Aplikasi Pembayaran SPP Berbasis WEB Menggunakan ISO/IEC 29119 - Rifki Ardiansyah; Satria Maulana; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
Software quality testing is an important step to ensure that an application meets user needs and applicable standards. The purpose of this study is to evaluate the quality of a Web-Based Tuition Payment Application, designed to assist tuition payment management in schools. The application is designed to assist tuition payment management. The results of the study indicate that the application meets most of the software quality criteria, especially in terms of functionality and usability, using functional and non-functional testing approaches based on the ISO/IEC 29119 framework. However, to maintain optimal quality, improvements are needed in the security and documentation sections of the testing.